The management reform of public universities - Cira de Pelekais (Telos: Revista de Estudios Interdisciplinarios en Ciencias Sociales, 2001)
The demands and challenges presented to Venezuelan Public Universities, at the beginning of the 21st century, impose and make necessary profound transformations in their organization and management schemes, in their relations with Public Administration entities and in their relations with the productive sector of the environment where they operate, likewise in their fundamental products and lines of work such as research, teaching and extension.